Chitooligosaccharides Prevents the Development of Colitis-Associated Colorectal Cancer by Modulating the Intestinal Microbiota and Mycobiota - Wu, Minna; Li, Jianmin; An, Yunying; Li, Puze; Xiong, Wancheng; Li, Jinsong; Yan, Dong; Wang, Mingyong; Zhong, Genshen (Frontiers in Microbiology, 2019)
Gut microbes play a crucial role in the development of colorectal cancer. Chitooligosaccharides (COS), are oligomer that are depolymerized from chitosan and possess a wide range of biological activities. In this study, the effects of COS on colorectal cancer (CRC) development were evaluated using azoxymethane and dextran sulphate sodium (AOM/DSS) induced mouse model of CRC (CACM). In the COS-treated CRC group (CMCOS), COS protected mice from CRC by decreasing the disease activity index, tumor incidences and multiplicity, and the mRNA levelS of COX-2, IL-6, TNF-α, IL-1β, IL-10 and IKK-β mRNA in colonic epithelial cells. The results of a cage-exchanged experiment, in which mice from the CACMe and CMCOSe treatments exchanged cages every day to interact with microbes, showed that gut microbes play an important role in preventing CAC by COS. The abundances of fecal bacteria (total bacteria, Lactobacillus, Enterococcus, Fusobacterium nucleatum and butyrate-producing bacteria) were detected by qPCR on the 0th, 1st, 3rd, 6th, 9th and 10th weekends. Furthermore, microbiota and mycobiota were analyzed by high-throughput sequencing on an Illumina MiSeq PE300 system. COS protected mice from CRC by reversing the imbalance of bacteria and fungi, especially by reducing the abundance of Escherichia-shigella, Enterococcus, and Turicibacter, and increasing the levels of Akkermansia, butyrate-producing bacteria and Cladosporium.